Patient Safety Culture Status and Its Predictors among Healthcare Workers - Mengistu Mitiku; Alemseged Aregay; Tesfay Hailu (International Journal of Public Health Science (IJPHS), 2018)
Good patient safety culture of healthcare professionals brings about fine consequences for patients. This study, therefore, aimed in evaluating the current status and predictors of safety culture among healthcare workers in Mekelle Zone hospitals, Tigray, Northern Ethiopia. A cross-sectional survey was conducted among 325 healthcare workers in three hospitals of Mekelle city from February to May, 2017. Simple random sampling technique was employed to select study subjects. Data was analyzed using SPSS. Logistic regression was used to determine the predictors of patient safety culture among healthcare workers at 95% confidence level and 5% level of significance. Statistical significance was set at p <0.05. Of the 325 Healthcare workers, 21.6% rated the culture of patient safety as satisfactory and 78.4% rated as unsatisfactory. Old aged healthcare workers (AOR=21.9, 95% of CI: 2.51-61.69) and ‘hospital management support for patient safety’ (AOR=2.68, 95% CI=1.06-6.79) were strong predictor of satisfactory patient safety culture. Satisfactory patient safety culture grade obtained was only 21.6%, indicating that health care professionals are not delivering patient centered service and there is a lot of work to be done in the hospitals to improve culture of patient safety among healthcare workers.